Meningkatkan Kemampuan Nilai-nilai Agama dengan Metode ‘Ibrah di Kelompok A TK Islam Al Husain Sawangan Depok - Winda Nidya Putri Fitriana; Elis Siti Maria Ulfah; Ernawati Ernawati (Jurnal Dirosah Islamiyah, 2022)
During the pandemic, learning for early childhood groups is carried out online. This adds to the difficulty of learning, especially in conveying religious values ​​to early childhood. In response to this, Islamic education offers the ibrah method. The use of this method is carried out through thinking, observing, and investigating by the rational power which is then digested by the heart by measuring the values ​​contained in it. In implementing the concept of ibrah, Classroom Action Research (CAR) was carried out. The author has conducted classroom action research in Group A, Al Husain Islamic Kindergarten, Sawangan, Depok. This effort was carried out in two cycles. Each cycle is carried out in five meetings. Cycle 1 is carried out by applying the ibrah method which involves elements of stories and observations of natural phenomena. Two of these things the achievement of the target is the divine aspect. While in cycle 2 apply learning with exemplary elements. The targets to be achieved are aspects of devotion/worship and exemplary. The two cycles are carried out to carry out the transformation and introduction of religious values, as well as efforts to increase religious values ​​to early childhood. The teacher elaborates between natural knowledge and several aspects of religious values ​​consisting of divinity, worship, and character. the ability to understand religious values ​​can be increased by the ibrah method. It can be seen from the results obtained from the pre-cycle that is equal to 64.16%, da cycle 1 is 71.06%, then increased to 76.9% in cycle 2. As a result, learning using the ibrah method is very effective in increasing the ability to understand religious values ​​for children. Keywords: Early childhood, Learning religious values, and Ibrah Method